Prioritas Pengembangan Jaringan Jalan di Kabupaten Ogan Komering Ulu (OKU) Selatan - Adrifan, Adrifan; Nisumanti, Sartika; Nazila, Iva (Universitas Batanghari Jambi, 2025)
The development of this road network needs to be done in order to know the effect of the road network in an area or a city that needs road network development or handling, both in the long, short and medium term. Network development can support growth in South OKU Regency by analyzing the level of accessibility of the road network to the influence of inter-regional connectivity, the influence of road conditions, and development alternatives in the context of road network development. This study aims to evaluate the accessibility of the road network in South OKU Regency, analyze the need for road network development based on the potential of natural resources and regional spatial plans (RT / RW) and accessibility outside the region. The method used is the FPCI (Fuzzy Pavement Conditions Index) Method. The result of this research is the analysis stated that the network development of some high potential areas and integrated tourism development areas of Lake Ranau still have low accessibility value so that road network development action is needed in the form of repair, widening and or adding road sections. High potential areas that have low accessibility ratings include Muaradua Kisam Subdistrict, Beringin Island Subdistrict, Buay Pemaca Subdistrict and Banding Agung Subdistrict and for accessibility out of the area on several roads in damaged condition so as to slow down the speed of the road.